Nonlinear and entropic velocity distribution in open channel. Issue 2 (3rd May 2016) - Tiwari, Harinarayan; Sharma, Nayan
Abstract: The present study describes the nonlinear vertical velocity distribution in an open channel (with and without hydraulic structure). Conventionally, velocity distribution is based on shear velocity normalization. In this study, maximum velocity has been applied for normalization. Von-Kármán logarithmic distribution (based on Kármán constant), its proposed analogous models, and entropy-based nonlinear velocity distribution have been compared for both the cases (with and without hydraulic structure). An entropy-based nonlinear velocity profile model has been also suggested to describe the velocity field in open channels. The suggested approach has been validated by means of controlled laboratory tests, executed in flume under steady flow conditions and at hydraulically smooth surface. The higher equivalence between the estimated velocity profiles using entropy and the observed ones. Entropy model has found best replicating model with respect to other four models (based on analogous of Prandtl–von Kármán model with the use of maximum velocity parameterization) but it also acquired difficulties regarding its higher number of numerically calculated coefficients. Power analogous model (based on maximum Reynolds number) and entropy model has been suggested as overall robust velocity distribution model and it is performing equally for both (with and without hydraulic structure) conditions.